Development of an UPLC-MS/MS Method for the Quantitative Analysis of Upadacitinib in Beagle Dog Plasma and Pharmacokinetics Study - Wang MJ; Zhao YH; Fan C; Wang YJ; Wang XQ; Qiu XJ; Shen RL (Dove Medical Press, 2021)
Meng-Jie Wang,1 Yu-Hang Zhao,2 Chen Fan,3 Ying-Jie Wang,3 Xin-Qi Wang,3 Xiang-Jun Qiu,3 Rui-Le Shen1 1Department of Neurology, The First Affiliated Hospital, and College of Clinical Medicine of Henan University of Science and Technology, Luoyang, Henan, 471003, People's Republic of China; 2School of Medical Imaging, Hangzhou Medical College, Hangzhou, 310051, Zhejiang, People's Republic of China; 3Department of Pharmacy, School of Basic Medical Sciences, Henan University of Science and Technology, Luoyang, 471023, Henan, People's Republic of ChinaCorrespondence: Xiang-Jun QiuDepartment of Pharmacy, School of Basic Medical Sciences, Henan University of Science and Technology, Luoyang, 471023, Henan, People's Republic of ChinaEmail lyxiangjun@126.comRui-Le ShenDepartment of Neurology, The First Affiliated Hospital, and College of Clinical Medicine of Henan University of Science and Technology, Luoyang, 471003, Henan, People's Republic of ChinaEmail yfyshenruile@126.comBackground: Upadacitinib, a novel selective Janus kinase 1 (JAK1) inhibitor, has been recently approved by the US FDA for the treatment of adult patients with moderately to severely active rheumatoid arthritis (RA). An ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method for the quantitative analysis of upadacitinib in beagle dog plasma was developed and validated.Methods: Upadacitinib and fedratinib (internal standard, IS) were extracted with ethyl acetate under alkaline condition and then separated and detected. The chromatographic column was Waters Acquity UPLC BEH C18 column (2.1 mm × 50 mm, 1.7 μm), the mobile phase was acetonitrile and 0.1% formic acid in water with gradient elution procedure, and the flow rate was 0.40 mL/min. Under the positive ion mode, upadacitinib and IS were monitored by multiple reaction monitoring (MRM) as the following mass transition pairs: m/z 447.00 → 361.94 for upadacitinib and m/z 529.82 → 141.01 for IS.Results: In the concentration range of 1- 500 ng/mL, upadacitinib had good linearity, and the lower limit of quantification (LLOQ) was 1 ng/mL. The RSD of the intra- and inter-day precision was less than 10.03%, and the RE of accuracy was − 3.79% to 2.58%. The extraction recovery of upadacitinib was more than 80%, the matrix effect was around 100%, and upadacitinib was found to be stable.Conclusion: The novel optimized UPLC-MS/MS assay was an effective tool for the determination of upadacitinib and had been successfully applied to the pharmacokinetic study of upadacitinib in beagle dogs, and this method would also be used to study DDIs.Keywords: upadacitinib, UPLC-MS/MS, pharmacokinetic, beagle dog